Cannabis lighting: Decreasing blue photon fraction increases yield but efficacy is more important for cost effective production of cannabinoids. - F Mitchell Westmoreland; Paul Kusuma; Bruce Bugbee (PLoS ONE)
LED technology facilitates a range of spectral quality, which can be used to optimize photosynthesis, plant shape and secondary metabolism. We conducted three studies to investigate the effect of blue photon fraction on yield and quality of medical hemp. Conditions were varied among studies to evaluate potential interactions with environment, but all environmental conditions other than the blue photon fraction were maintained constant among the five-chambers in each study. The photosynthetic photon flux density (PPFD, 400 to 700 nm) was rigorously maintained at the set point among treatments in each study by raising the fixtures. The lowest fraction of blue photons was 4% from HPS, and increased to 9.8, 10.4, 16, and 20% from LEDs. There was a consistent, linear, 12% decrease in yield in each study as the fraction of blue photons increased from 4 to 20%. Dry flower yield ranged from 500 to 750 g m-2. This resulted in a photon conversion efficacy of 0.22 to 0.36 grams dry flower mass yield per mole of photons. Yield was higher at a PPFD of 900 than at 750 μmol m-2 s-1. There was no effect of spectral quality on CBD or THC concentration. CBD and THC were 8% and 0.3% at harvest in trials one and two, and 12% and 0.5% in trial three. The CBD/THC ratio was about 25 to 1 in all treatments and studies. The efficacy of the fixtures ranged from 1.7 (HPS) to 2.5 μmol per joule (white+red LED). Yield under the white+red LED fixture (10.4% blue) was 4.6% lower than the HPS on a per unit area basis, but was 27% higher on a per dollar of electricity basis. These findings suggest that fixture efficacy and initial cost of the fixture are more important for return on investment than spectral distribution at high photon flux.